2000
DOI: 10.1177/152660280000700301
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Aneurysm Size and Graft Behavior after Endovascular Stent-Grafting: Clinical Experiences and Observations over 3 Years

Abstract: Although endoleaks after aortic stent-graft placement tend to cause ongoing aneurysm growth, we have also observed aneurysm shrinkage despite ongoing endoleak. The presence or absence of an endoleak in itself may be a poor predictor of successful stent-graft therapy. Lifelong surveillance is needed to assure successful aneurysm exclusion and stability or shrinkage of the aneurysm sac. Technical improvements in stent materials and design are necessary to guarantee long-term stability and safety of the device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
6

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 26 publications
1
28
0
6
Order By: Relevance
“…20 Rates of aneurysm growth following EVAR of large AAAs have been reported to vary between 1% and 28% during intermediate follow-up, and this is partly explained by the different methods used to calculate this outcome (as illustrated in Results). 21,22 We only detected 5 incidences of AAA rupture during follow-up, suggesting that follow-up and reintervention were generally protecting patients from severe consequences ( Table 2). However, since our follow-up is limited, rupture rates for these size aneurysms is low (1.9%-3.2% at 5 years, Table 3), and most patients do not have postmortems, this finding should be viewed with caution.…”
Section: Discussionmentioning
confidence: 82%
“…20 Rates of aneurysm growth following EVAR of large AAAs have been reported to vary between 1% and 28% during intermediate follow-up, and this is partly explained by the different methods used to calculate this outcome (as illustrated in Results). 21,22 We only detected 5 incidences of AAA rupture during follow-up, suggesting that follow-up and reintervention were generally protecting patients from severe consequences ( Table 2). However, since our follow-up is limited, rupture rates for these size aneurysms is low (1.9%-3.2% at 5 years, Table 3), and most patients do not have postmortems, this finding should be viewed with caution.…”
Section: Discussionmentioning
confidence: 82%
“…Endovascular therapy has now been established as a technically feasible option and many reports have provided excellent short-term results. [1][2][3][4] The long-term outcome after this treatment, however, is often complicated because of endoleaks. 7 The postoperative results would be excellent and on a par with conventional replacement surgery if a complete prevention of endoleaks could be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] The rate of shrinkage, however, is variable, and more than half of the aneurysms do not decrease in size. 3 In general, the pulsatile pressure within the aneurysm sac due to endoleaks prevents shrinkage and tends to cause aneurysmal growth after this treatment.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Patients who underwent only noncontrast CT scan after EVAR were excluded because it has been reported that there were some paradoxical cases of aneurysm shrinkage in patients with persistent endoleak. 10,11) …”
Section: Measurement Of the Aortic Sizementioning
confidence: 99%